The complete chloroplast genome of Blastus auriculatus (Melastomataceae). Issue 1 (2nd January 2019) - Tan, Guangwen; Han, Bingqian; Wang, Yongqi; Li, Zihua; Zhao, Yangyang; Luo, Shuai; Liu, Xiaozhou; Liu, Ying; Zhou, Qiujie
Abstract: Blastus auriculatus, a shrub sparsely distributed in Yunnan, China, occurs only in bamboo forests at an elevation of below 200 m. It is categorized as 'Critically Endangered (CR)' in China Biodiversity Red List. In addition, the phylogenetic position of Blastus within the Melastomataceae family is still unclear. This study generated the complete chloroplast genome sequence of B. auriculatus with aims to provide genetic resources for conservation genetics and to reslove the phylogenetic position of Blastus . The size of the chloroplast genome of B. auriculatus is 155, 981 bp, including a large single-copy (LSC) region of 85, 955 bp and a small single-copy (SSC) region of 16, 434 bp, separated by a pair of identical inverted repeat regions (IRs) of 26, 796 bp each. The chloroplast genome contains a total of 125 genes, including 80 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis showed that B. auriculatus is closest to Barthea barthei among species in Melastomataceae with available chloroplast genome sequences.